2020
DOI: 10.2147/ceg.s254278
|View full text |Cite
|
Sign up to set email alerts
|

<p>Relationship Between Vitamin D Deficiency and Disease Activity in Patients with Inflammatory Bowel Disease in Ahvaz, Iran</p>

Abstract: Background and Aims: Previous studies have shown that vitamin D plays an important role in inflammatory bowel disease (IBD). This study was designed to investigate the relationship between vitamin D levels and disease activity in IBD patients in Ahvaz, Iran. Methods: This cross-sectional study was conducted on adult IBD patients referring to the outpatient clinic of gastroenterology at Imam Khomeini Hospital in Ahvaz city, in the southwest of Iran. Each patient's disease activity defined according to Crohn's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…Vitamin D insufficiency is associated with AID development such as MS [52,53,57], RA [54][55][56][57], insulin-dependent diabetes mellitus [51], and IBD [53,[57][58][59]217] (Table 2). The role of vitamin D in autoimmune diseases was reviewed by [57,60,186].…”
Section: Low Concentration Of Vitamin D and Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D insufficiency is associated with AID development such as MS [52,53,57], RA [54][55][56][57], insulin-dependent diabetes mellitus [51], and IBD [53,[57][58][59]217] (Table 2). The role of vitamin D in autoimmune diseases was reviewed by [57,60,186].…”
Section: Low Concentration Of Vitamin D and Autoimmune Diseasesmentioning
confidence: 99%
“…High titers of various AABs are present in pulmonary TB patients with vitamin D deficiency [48][49][50][51]. Vitamin D deficiency was registered in multiple sclerosis (MS) [52,53], rheumatoid arthritis (RA) [54][55][56][57], and inflammatory bowel disease [53,[57][58][59]. The role of vitamin D in autoimmune diseases was demonstrated in [57,60].…”
Section: Introductionmentioning
confidence: 99%
“… 165 In addition, Ko et al found a negative correlation between disease activity and vitamin D levels in CD but not in UC patients, 74 and Rasouli et al showed that patients with active disease are more likely to have low vitamin D levels than those in UC remission. 77 Moreover, serum bioactive vitamin D status was inversely correlated with fecal calprotectin (FC) during IBD, but not with systemic inflammation markers such as CRP, white cell count, and platelet count, indicating that vitamin D correlated negatively with intestinal but not systemic inflammation. 166 Other studies have also shown a highly inverse correlation between vitamin D concentration and disease activity ( Table 2 ).…”
Section: Predictive Role For Vitamin D During Ibdmentioning
confidence: 99%
“…When produced by plants and fungus, it is named ergocalciferol (VD2), and when produced in the skin, it is called cholecalciferol (VD3): 1,25-dihydroxyvitamin D3 1,25(OH)2D3. The active form, 1,25 (OH)2D3, is associated with biological effects [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%